Heat Distribution in the Southeast Pacific Is Only Weakly Sensitive to High‐Latitude Heat Flux and Wind Stress. Issue 12 (8th December 2019) - Jones, Daniel C.; Boland, Emma; Meijers, Andrew J.S.; Forget, Gael; Josey, Simon A.; Sallee, Jean‐Baptiste; Shuckburgh, Emily
Abstract: The Southern Ocean features regionally varying ventilation pathways that transport heat and carbon from the surface ocean to the interior thermocline on timescales of decades to centuries, but the factors that control the distribution of heat along these pathways are not well understood. In this study, we use a global ocean state estimate (ECCOv4) to (1) define the recently ventilated interior Pacific (RVP) using numerical passive tracer experiments over a 10‐year period and (2) use an adjoint approach to calculate the sensitivities of the RVP heat content (RVPh) to changes in net heat flux and wind stress. We find that RVPh is most sensitive to local heat flux and wind stress anomalies north of the sea surface height contours that delineate the Antarctic Circumpolar Current, with especially high sensitivities over the South Pacific Gyre. Surprisingly, RVPh is not especially sensitive to changes at higher latitudes. We perform a set of step response experiments over the South Pacific Gyre, the subduction region, and the high‐latitude Southern Ocean. In consistency with the adjoint sensitivity fields, RVPh is most sensitive to wind stress curl over the subtropical gyre, which alter isopycnal heave, and it is only weakly sensitive to changes at higher latitudes. Our results suggest that despite the localized nature of mode water subduction hot spots, changes in basin‐scale pressure gradients are an important controlling factor on RVPh. Because basin‐scale wind stress is expected to change in the coming decades to centuries, our results may have implications for climate, via the atmosphere/ocean partitioning of heat. Key Points: The heat content of the recently ventilated Pacific (RVPh) is strongly controlled by gyre circulation On timescales shorter than 3–5 years, RVPh is most sensitive to midlatitude wind stress anomalies On timescales longer than 3–5 years, RVPh is most sensitive to midlatitude heat flux anomalies